Impact of Ionic Liquid Structure and Loading on Gas Sorption and Permeation for ZIF-8-Based Composites and Mixed Matrix Membranes - Ortiz-Albo, Paloma (2022)
Carbon dioxide (CO2) capture has become of great importance for industrial processes due to the adverse environmental effects of gas emissions. Mixed matrix membranes (MMMs) have been studied as an alternative to traditional technologies, especially due to their potential to overcome the practical limitations of conventional polymeric and inorganic membranes. In this work, the effect of using different ionic liquids (ILs) with the stable metal–organic framework (MOF) ZIF-8 was evaluated. Several IL@ZIF-8 composites and IL@ZIF-8 MMMs were prepared to improve the selective CO2 sorption and permeation over other gases such as methane (CH4) and nitrogen (N2). Different ILs and two distinct loadings were prepared to study not only the effect of IL concentration, but also the impact of the IL structure and affinity towards a specific gas mixture separation. Single gas sorption studies showed an improvement in CO2/CH4 and CO2/N2 selectivities, compared with the ones for the pristine ZIF-8, increasing with IL loading. In addition, the prepared IL@ZIF-8 MMMs showed improved CO2 selective behavior and mechanical strength with respect to ZIF-8 MMMs, with a strong dependence on the intrinsic IL CO2 selectivity. Therefore, the selection of high affinity ILs can lead to the improvement of CO2 selective separation for IL@ZIF-8 MMMs